2017
DOI: 10.4238/gmr16039700
|View full text |Cite
|
Sign up to set email alerts
|

Research Article First cytotoxic, genotoxic, and antigenotoxic assessment of Euterpe oleracea fruit oil (açaí) in cultured human cells.

Abstract: ABSTRACT. Euterpe oleracea Mart., popularly known as "açaí", is a tropical fruit from the Amazon region where it has considerable economic importance. Açaí has been used as food and for several medicinal purposes. Despite the widespread use of this fruit, there is 2 E.S. Marques et al. Genetics and Molecular Research 16 (3): gmr16039700 a lack of data regarding the safety of using this fruit oil exclusively. Therefore, we evaluated the in vitro cytotoxic, genotoxic, and antigenotoxic effects of E. oleracea fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…A total of 60 publications were identified in the databases; however, 31 were duplicate articles. Among the 29 articles selected, 20 were excluded based on the titles and abstracts because they did not meet the inclusion criteria: 2 were literature reviews [ 7 , 24 ]; 6 did not study açaí in an animal model of cancer and/or did not perform a toxicological analysis [ 25 30 ]; 10 were in vitro studies [ 13 , 20 , 31 38 ]; and 2 did not use the order Rodentia [ 21 , 39 ]. After reading the full texts 9 articles were included for their critical evaluations of the safety and effectiveness of açaí in animal experimental models [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 60 publications were identified in the databases; however, 31 were duplicate articles. Among the 29 articles selected, 20 were excluded based on the titles and abstracts because they did not meet the inclusion criteria: 2 were literature reviews [ 7 , 24 ]; 6 did not study açaí in an animal model of cancer and/or did not perform a toxicological analysis [ 25 30 ]; 10 were in vitro studies [ 13 , 20 , 31 38 ]; and 2 did not use the order Rodentia [ 21 , 39 ]. After reading the full texts 9 articles were included for their critical evaluations of the safety and effectiveness of açaí in animal experimental models [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, açaí has been shown to have pharmacological properties including antiinflammatory, antioxidant, cardioprotective and anticancer activities [ 1 , 7 9 , 18 , 19 ]. Furthermore, açaí was not shown to be genotoxic in vitro and in vivo studies conducted, in cultured human lymphocytes and hepatoma cell lines [ 20 ], in rodents [ 21 ] and in humans [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Edible mushrooms are regarded as non-toxic and safe, but recent investigations reported that some of them cause DNA damages [27]. Numerous studies showed that the CBMN assay is a valid test for detection of genomic damage caused both in vitro [28,29] and in vivo [30,31]. Our results of CBMN assay showed that the extract was genotoxic in higher tested concentrations.…”
Section: Cytotoxic Activitymentioning
confidence: 55%
“…However, it has been reported that phenolic compounds, especially those belonging to the anthocyanin class, are able to help in the prevention and/or treatment of the disease. As a genotoxic assessment revealed the absence of significant DNA and chromosome damage in human HepG2 cells when treated with açai extract [ 16 ], we used HepG2 cells to mimic steatosis [ 17 ], and primary adipocyte cells, treated with TNF-α, as a model of persistent subcutaneous fat accumulation induced by an inflammatory state in vitro [ 18 ]. In the present study, we analyzed the effect of açai extract on the reduction of inflammatory states, highlighted its ability to modulate oxidative stress in combination with fat deposit accumulation, and revealed its potent effect to reduce key biomarkers related to fat accumulation.…”
Section: Introductionmentioning
confidence: 99%